Visualization of the Dynamics of Gene Expression in the Living Mouse - Amy Ryan; Heidi Scrable (Molecular Imaging)
Reporter genes can monitor the status and activity of recombinant genomes in a diverse array of organisms, from bacteria and yeast to plants and animals. We have combined luciferase reporter genes with a conditional gene expression system based on regulatory elements from the lac Operon of Escherichia coli to visualize the dynamics of gene expression in realtime in the living mouse. Using this technology, we have determined the rate of gene induction and repression, the level of target gene activity in response to different doses of inducer, and the schedule of induction during early embryogenesis of both the endogenous and the experimentally manipulated programs of mammalian gene expression associated with the HD/Hdh locus. The combination of in vivo imaging and lac regulation is a powerful tool for generating conditional transgenic mice that can be screened rapidly for optimal regulation and expression patterns, and for monitoring the induction and repression of regulated genes noninvasively in the living animal.